De novo assembly and comparative analysis of cherry (Prunus subgenus Cerasus) mitogenomes - Zhai, Tianya; Zhao, Zhuang; Fu, Chenlong; Huang, Lizhen; Jiang, Changci; Li, Meng; Wang, Zefu; Yang, Xiaoyue (Frontiers in Plant Science, 2025)
Prunus subgenus Cerasus (Mill) A. Gray, commonly known as cherries and cherry blossoms, possesses significant edible and ornamental value. However, the mitochondrial genomes (mitogenomes) of cherry species remain largely unexplored. Here, we successfully assembled the mitogenomes of five cherry species (P. campanulata, P. fruticosa, P. mahaleb, P. pseudocerasus, and P. speciosa), revealing common circular structures. The assembled mitogenomes exhibited sizes ranging from 383,398 bp to 447,498 bp, with GC content varying between 45.54% and 45.76%. A total of 62 to 69 genes were annotated, revealing variability in the copy number of protein-coding genes (PCGs) and tRNA genes. Mitogenome collinearity analysis indicated genomic rearrangements across Prunus species, driven by repetitive sequences, particularly dispersed repeats. Additionally, the five cherry species displayed highly conserved codon usage and RNA editing patterns, highlighting the evolutionary conservation of the mitochondrial PCGs. Phylogenetic analyses confirmed the monophyly of subg. Cerasus, although notable phylogenetic incongruences were observed between the mitochondrial and plastid datasets. These results provide significant genomic resources for forthcoming studies on the evolution and molecular breeding of cherry mitogenomes, enhancing the overall comprehension of mitogenome structure and evolution within Prunus.